If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -6x = 3(6x + -2) Reorder the terms: 9 + -6x = 3(-2 + 6x) 9 + -6x = (-2 * 3 + 6x * 3) 9 + -6x = (-6 + 18x) Solving 9 + -6x = -6 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 9 + -6x + -18x = -6 + 18x + -18x Combine like terms: -6x + -18x = -24x 9 + -24x = -6 + 18x + -18x Combine like terms: 18x + -18x = 0 9 + -24x = -6 + 0 9 + -24x = -6 Add '-9' to each side of the equation. 9 + -9 + -24x = -6 + -9 Combine like terms: 9 + -9 = 0 0 + -24x = -6 + -9 -24x = -6 + -9 Combine like terms: -6 + -9 = -15 -24x = -15 Divide each side by '-24'. x = 0.625 Simplifying x = 0.625
| Y-17=-18 | | 3n+1=11 | | 4x^2-32x+y^2+8y+64=0 | | x-2x-3x=-14 | | 5Y=-3X+20 | | n+14=86 | | 2(c-1)=c-7 | | 3x+11=x-5 | | 82=b-17 | | 5-(n+3)+3n+7=n+5 | | y^2-10y+40=0 | | 6n^2+10n-4=0 | | 8g=xmg | | 3.5(6x+6)= | | Y-25=50 | | 3x+10+2x+40+1x+10= | | y=5x^4-17 | | 42=8m-2m | | 4x-1/2=1/6 | | 197=7r-6-7(6r+6) | | 3(m+1)+2m=0 | | 2n+10=14+3n | | 8x/9=1/2 | | 3x^3/4=-24 | | 3.236(5.3m-7.9)-1.9m=65.369 | | ax-c=N | | 2a+14a+-11a=-15 | | -10x^2-18x=0 | | 9/17=3/a | | 99=11x | | 99=-6g | | t+2t-2t=8 |